Innovative Digital Technologies in Education and Business at the Third Annual Silesian Science Festival 2019 - Smyrnova-Trybulska, Eugenia; Zegzuła, Dominika; Staniek, Dawid (International Journal of Research in E-learning, 2020)
The Silesian Science Festival is an annual event organised by the University of Silesia in Katowice in cooperation with the Silesian University of Technology, Medical University of Silesia, the Jan Długosz University in Częstochowa, Academy of Fine Arts in Katowice, and The Jerzy Kukuczka Academy of Physical Education in Katowice. At the festival, specialists from almost all scientific/academic fields meet in one place.